1983
DOI: 10.1097/00006254-198307000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Haemoconcentration in Severe Pre-eclampsia

Abstract: The last maternal haemoglobin (Hb) concentration before delivery was related to the perinatal outcome in 87 non-anaemic women suffering from severe pre-eclampsia. Abnormally high Hb concentrations were found in most women with evidence of placental dysfunction. An inverse correlation was found between the centile weight of the newborn and the maternal Hb. Significantly higher Hb levels were found in pregnancies complicated by fetal growth retardation and perinatal distress compared with those in pregnancies wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…On the other hand, low Hb levels due to physiologic hemodilution are favourable for fetal growth [169]. Low Hbconcentrations (9.0-11.9 g/100 ml) are connected to reduced IUGR development in smokers, probably because of hemodilution and reduced blood viscosity favourable to uteroplacental circulation [79].…”
Section: Hemoglobin and S-ferrtinmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, low Hb levels due to physiologic hemodilution are favourable for fetal growth [169]. Low Hbconcentrations (9.0-11.9 g/100 ml) are connected to reduced IUGR development in smokers, probably because of hemodilution and reduced blood viscosity favourable to uteroplacental circulation [79].…”
Section: Hemoglobin and S-ferrtinmentioning
confidence: 99%
“…High Hb levels, from 10 weeks' gestation through the second and third trimester, are therefore associated with increased frequency of preeclampsia and IUGR [169,[174][175][176][177].…”
Section: Hemoglobin and S-ferrtinmentioning
confidence: 99%
“…In a previous investigation we have shown that during severe pre-eclampsia the maternal hemoglobin concentration (Hb) is inversely correlated to the weight centile of the newborn. In addition we found that abnormally high Hb levels were closely associated with perinatal distress and particularly perinatal death (10). Thus, the maternal Hb-test has turned out to be a useful indicator of fetal growth and wellbeing.…”
mentioning
confidence: 78%
“…122 ' 123 An insufficient plasma volume expansion is reflected in the clinical sign of a high or rising haemoglobin concentration or haematocrit. 124 In a retrospective study of over 54 000 singleton pregnancies, Murphy et al 125 showed a highly significant correlation in both nulliparae and multiparae between haemoglobin concentration at first booking and the incidence of hypertensive disorders. With increasing haemoconcentration, the circulatory properties of the blood will change.…”
Section: Signs Of Haemodynamic Maladaptationmentioning
confidence: 99%